1999
DOI: 10.1097/00007691-199904000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole Bioequivalence Study: Quantification by Tandem Mass Spectrometry

Abstract: To develop a new method for quantifying fluoconazole in human plasma and to compare the bioavailability of two fluconazole capsule formulations, an open, randomized, two-period crossover study with a one-week washout interval was conducted in 24 healthy volunteers. Plasma samples were obtained up to 168 hours after drug administration and the serum fluconazole concentrations were analyzed using electrospray tandem mass spectrometry coupled to liquid chromatography using multiple reaction monitoring mode. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
3
12
0
1
Order By: Relevance
“…1 of 0.108 to 0.023 h À1 [1,6]. These values are similar to the corresponding values obtained in the current study, suggesting that ethnicities may have little or no effect on the elimination process, half-life or extent of absorption of fluconazole.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1 of 0.108 to 0.023 h À1 [1,6]. These values are similar to the corresponding values obtained in the current study, suggesting that ethnicities may have little or no effect on the elimination process, half-life or extent of absorption of fluconazole.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies from Brazil [1,6] and Thailand [7] reported a K el of 0.021 to 0.023 h À1 [1,7], T max of 1.18 to 1.59 h [7], C max of 2.61 to 3.84 mg/ml [1,6], AUC 0!1 of 152 to 181 mg.h/ml [1,6] and C max /AUC 0 ! 1 of 0.108 to 0.023 h À1 [1,6].…”
Section: Resultsmentioning
confidence: 94%
“…The analytical techniques employed in recent years for the estimation of sertraline in human plasma include HPLC, GC or in combination with MS i.e. liquid chromatography and tandem mass spectrometry (LC-MS/MS) and GC-MS/MS [7][8][9][10][11][12][13][14][15][16][17][18]. All these reported methods require either a lengthy extraction and/or derivatization procedure, yet the desired sensitivity is not achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [13] have reported a GC-MS/MS method with sensitivity of 0.2 ng/ml, but the extraction procedure involved deproteination, liquid-liquid extraction followed by derivatization. The upper limit of quantification (10.0 ng/ml) of their linearity range (0.2-10 ng/ml) for sertraline is inadequate to quantify the achieved C max for 50 mg [7] as well as for 100 mg dose [8]. Also, these assay methods do not meet modern drug development needs, which require a rapid and accurate feedback of analytical information of pre-clinical and clinical pharmacokinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods using liquid chromatography coupled with triple-quadrupole mass spectrometry (LC-MS/MS) have been reported for the quantification of single antifungals in biological fluids, including fluconazole (FLC) (14,34,49), itraconazole (ITZ) (39,62) and its active metabolite (hydroxyitraconazole [OH-ITZ]) (4,6,27,53), voriconazole (VRC) (2,15,26,54,63), posaconazole (PSC) (10, 40a, 44, 52), caspofungin (CASPO) (7,16,40), and anidulafungin (ANI) (13). LC-MS/MS assays were recently reported for the simultaneous quantification of posaconazole, voriconazole, isavuconazole, caspofungin, anidulafungin, and micafungin in different peripheral blood compartments (19) and of itraconazole, voriconazole, and posaconazole in blood (3).…”
mentioning
confidence: 99%